1986
DOI: 10.1007/bf00178503
|View full text |Cite
|
Sign up to set email alerts
|

Chronic use of benzodiazepines and psychomotor and cognitive test performance

Abstract: The performance of 43 long-term users (average = 5 years) of benzodiazepine (BZ) medications was examined on a battery of behavioral tasks, cognitive tests, and subjective mood rating scales. The performance of the chronic BZ users did not differ significantly from age- and sex-matched anxious subjects, except that critical flicker fusion (CFF) thresholds were lower and subjective ratings of tranquilization were higher in the BZ users. Twenty-two subjects were reexamined in order to determine the acute effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
61
4
4

Year Published

1987
1987
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(76 citation statements)
references
References 33 publications
7
61
4
4
Order By: Relevance
“…In patients taking high doses of benzodiazepines for at least one year there was marked tolerance to the psychomotor effects of a test dose of lorazepam; little tolerance was shown in patients taking low doses for one to eleven months (Aranko et al 1985ft). In long-term benzodiazepine users, the anxiolytic effect, reduction of critical flicker fusion threshold and the short-term memory impairments induced by benzodiazepines were found to persist, whereas there was no longer any psychomotor impairment or sedation (Lucki et al 1986). This suggests that tolerance had developed to the latter effects, but not to the former.…”
Section: Tolerancementioning
confidence: 96%
See 1 more Smart Citation
“…In patients taking high doses of benzodiazepines for at least one year there was marked tolerance to the psychomotor effects of a test dose of lorazepam; little tolerance was shown in patients taking low doses for one to eleven months (Aranko et al 1985ft). In long-term benzodiazepine users, the anxiolytic effect, reduction of critical flicker fusion threshold and the short-term memory impairments induced by benzodiazepines were found to persist, whereas there was no longer any psychomotor impairment or sedation (Lucki et al 1986). This suggests that tolerance had developed to the latter effects, but not to the former.…”
Section: Tolerancementioning
confidence: 96%
“…Thus one would expect little tolerance to be manifested in critical flicker fusion (e.g. Lucki et al 1986). In agreement with this suggestion, when nitrazepam (10 mg) or temazepam (20 mg) were given at night for 10 nights, no tolerance could be detected when volunteers were challenged with a test dose of lorazepam .…”
Section: Tolerancementioning
confidence: 99%
“…Some data indicate that long-term benzodiazepine use (average = 5 years) is not associated with psychomotor impairment. 16 Data on long-term benzodiazepine use are important, as these agents have been recommended for the long-term treatment of panic disorder 17 and in combination with SSRIs for treatmentrefractory panic disorder. 18 In addition, a large prospective, longitudinal study involving 443 patients with panic disorder found that benzodiazepines were the most commonly used psychotropic medication for this condition.…”
Section: Letters To the Editormentioning
confidence: 99%
“…c) L'absence d'une tolérance complète aux effets des BZD sur la mémoire serait un autre fait appuyant l'idée d'un déficit de la mémoire. La tolérance aux effets sédatifs et hypnotiques des BZD est bien documentée dans la littérature (Lucki et al, 1986 ;File, 1985 ;Sellal et al, 1994). Toutefois, il n'y aurait qu'une tolérance partielle qui se développerait pour l'effet « amné-siant » des BZD (Lucki et al, 1986 ;Sellal et al, 1994 ;Gorenstein et al, 1994), laissant place à des effets délétères résiduels sur la mémoire des gens âgés.…”
Section: De L'approche Expérimentale à La Clinique Quotidienneunclassified
“…La tolérance aux effets sédatifs et hypnotiques des BZD est bien documentée dans la littérature (Lucki et al, 1986 ;File, 1985 ;Sellal et al, 1994). Toutefois, il n'y aurait qu'une tolérance partielle qui se développerait pour l'effet « amné-siant » des BZD (Lucki et al, 1986 ;Sellal et al, 1994 ;Gorenstein et al, 1994), laissant place à des effets délétères résiduels sur la mémoire des gens âgés. Un autre fait intéressant concernant la tolérance a été rapporté par Bertz et al (1997) qui démontrent que la tolérance serait généralement plus lente à se développer chez les personnes âgées que chez les plus jeunes laissant encore une fois présager des effets prolongés sur le fonctionnement mnésique.…”
Section: De L'approche Expérimentale à La Clinique Quotidienneunclassified